Post-harvest treatments of polyamines influence shelf-life and quality of kiwifruit (Actinidia deliciosa) - JHALEGAR, MD JAMEEL; SHARMA, R R; PAL, R K (The Indian Journal of Agricultural Sciences, 2012)
Kiwifruit cv. Allison fruits were treated with different concentrations of PAs like SPM and SPD by immersion method and stored at ambient conditions (22 ± 4°C and 65– 70% R H) for 15 days. Our results revealed that untreated fruits showed high physiological loss in weight (10.6%) even on 9th day of storage, whereas SPM or SPD treated fruits showed very less PLW even on 15th day. PAs treated fruits showed lesser ethylene evolution rate than untreated fruits at different intervals. Similarly, TSS showed sudden increase in the untreated fruits even on 6th day, increased at a sharper rate up to 12th and then declined, whereas PAs treated fruits started showing increase in TSS from 9th day only. SPM @ 1.5 mM was the best treatment to increase the shelf-life of kiwifruit up to 15 days.